Genomic characterization revealing the high rate of tet(X4)-positive Escherichia coli in animals associated with successful genetic elements - Shao, Li; Wu, Changbu; Li, Chengjuan; He, Ruowen; Chen, Guanping; Sun, Dandan; Yang, Yanxian; Feng, Yu; Zhang, Guili; Yan, Bin; Dai, Min; Tian, Guo-Bao; et al. (Frontiers in Microbiology, 2024)
The rapid spread of plasmid-mediated tet(X4) conferring high tigecycline resistance poses a significant threat to public health. Escherichia coli as the most common pathogen which carries tet(X4) has been widely disseminated in China. Thus, comprehensive investigations are required to understand the mechanism of transmission of tet(X4)positive E. coli. In this study, a total of 775 nonduplicate samples were collected in Guangdong, China from 2019 to 2020. We screened for tet(X4)-positive E. coli by PCR amplification and species identification. Furthermore, we analyzed the phylogenetics and genetic context of tet(X4)-positive E. coli through whole-genome sequencing and longreads sequencing. Overall, 146 (18.84%) tet(X4)-positive E. coli were isolated, comprising 2 isolates from humans and 144 isolates from pigs. The majority of tet(X4)-positive E. coli exhibited resistance to multiple antibiotics but all of them were susceptible to amikacin and colistin. Phylogenetic analysis showed that ST877, ST871, and ST195 emerged as the predominant sequence types in tet(X4)-positive E. coli. Further analysis revealed various genetic environments associated with the horizontal transfer of tet(X4). Notably, a 100-kbp large fragment insertion was discovered downstream of tet(X4), containing a replicon and a 40-kbp gene cluster for the bacterial type IV secretion system. The high colonization rate of tet(X4)-positive E. coli in animals suggests that colonization as a key factor in its dissemination to humans. Diverse genetic context may contribute to the transfer of tet(X4).Our findings underline the urgent need for controlling the spread of plasmid-mediated tigecycline resistance.